2022
DOI: 10.2196/36690
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Wearables on Health Care Outcomes in Chronic Disease: Systematic Review

Abstract: Background Chronic diseases contribute to high rates of disability and mortality. Patient engagement in chronic disease self-management is an essential component of chronic disease models of health care. Wearables provide patient-centered health data in real time, which can help inform self-management decision-making. Despite the perceived benefits of wearables in improving chronic disease self-management, their influence on health care outcomes remains poorly understood. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…Historically, data may have nested within the evidence domain; however, rapid digital transformation of society and healthcare is creating new models of precision public health based upon real-world and big data [ 6 , 10 , 27 ]. Data is not synonymous with evidence; for example, lifestyle wearable devices such as smartwatches generate personal health information in real-time but most do not meet the data accuracy regulatory standards required for medical equipment [ 28 ]. More data does not also automatically mean more information, and information is not automatically evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, data may have nested within the evidence domain; however, rapid digital transformation of society and healthcare is creating new models of precision public health based upon real-world and big data [ 6 , 10 , 27 ]. Data is not synonymous with evidence; for example, lifestyle wearable devices such as smartwatches generate personal health information in real-time but most do not meet the data accuracy regulatory standards required for medical equipment [ 28 ]. More data does not also automatically mean more information, and information is not automatically evidence.…”
Section: Discussionmentioning
confidence: 99%
“…One recent systematic review examined the impact of wearables on health care outcomes in patients with chronic diseases, but only a small number of these studies examined costs. 104 A simulated model suggested that AF screening with wearable devices is cost-effective compared with no screening or traditional methods (ie, pulse palpation and 12-lead ECG), 103 and an economic evaluation of a cardiac telerehabilitation program suggested that it was likely to be cost-effective compared with traditional center-based CR. 45 As the existing body of evidence for wearables in cardiovascular medicine grows, it will be important for these studies to also publish cost analyses.…”
Section: Costs Associated With Clinical Usementioning
confidence: 99%
“…The evidence behind the use of smartwatches in chronic disease prevention is limited. Most studies have adopted an observational research design and/or have small sample sizes 14 . Providing a comprehensive analysis of an individual's health in real time could enable individualised care for people with chronic disease.…”
Section: The Current Role Of Smartwatches In Chronic Disease Preventionmentioning
confidence: 99%